2016
DOI: 10.1098/rstb.2015.0418
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and ATP control multiple vital functions

Abstract: Life on Planet Earth, as we know it, revolves around adenosine triphosphate (ATP) as a universal energy storing molecule. The metabolism of ATP requires a low cytosolic Ca 2+ concentration, and hence tethers these two molecules together. The exceedingly low cytosolic Ca 2+ concentration (which in all life forms is kept around 50–100 nM) forms the basis for a universal intracellular signalling system in which Ca 2+ acts as a second messenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Although cells relevant to exocrine and endocrine functions of the pancreas have been extensively studied and well described in the literature (Hegyi & Petersen, ; Petersen & Verkhratsky, ), a type of pancreatic auxiliary cells was overlooked until recently. Initially observed in 1982 (Watari et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cells relevant to exocrine and endocrine functions of the pancreas have been extensively studied and well described in the literature (Hegyi & Petersen, ; Petersen & Verkhratsky, ), a type of pancreatic auxiliary cells was overlooked until recently. Initially observed in 1982 (Watari et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although cells relevant to exocrine and endocrine functions of the pancreas have been extensively studied and well described in the literature (Hegyi & Petersen, 2013;Petersen & Verkhratsky, 2016), a type of pancreatic auxiliary cells was overlooked until recently. Initially observed in 1982 (Watari et al 1982) as vitamin A storing cells, then identified, characterised and isolated for the first time in 1998 (Apte et al 1998;Bachem et al 1998), pancreatic stellate cells (PSCs) are currently attracting interest predominantly due to their well-documented role in pancreatic fibrosis (Apte et al 2012(Apte et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal [Ca 2+ ] i , varies depending on the cell type. Cytosolic calcium effects the efficiency of ATP production via the tricarboxylic acid cycle (TCA) cycle coupled to the electron transport chain (ETC) [13], with transient increases of [Ca 2+ ] I stimulating mitochondrial respiration. In contrast, persistent high levels of [Ca 2+ ] i cause cellular damage leading to cell death [1].…”
Section: Introductionmentioning
confidence: 99%
“…Because Ca 2+ can interact with many potential cellular targets, signalling precision requires localized rises of the cytosolic [Ca 2+ ] ([Ca 2+ ] i ) (Petersen et al . ; Petersen & Verkhratsky, ). In the nervous system, the extremely precise control of presynaptic neurotransmitter secretion depends on close co‐localization of voltage‐gated Ca 2+ channels and the exocytotic machinery (Südhof, ).…”
Section: Introductionmentioning
confidence: 99%